Strengthening Online Education And Improving Bojong Village Community Awareness Against Covid-19 - Teten Mohamad Sapril Mubarok; Hendi Hidayat; Elda Radiani; Gaizka Izmi Fahrena; Riani Badriah (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract Through the New Covid-19 Thematic KKN 2020, we are required to increase awareness and resilience of the community in facing the Covid-19 outbreak in an effort to create a healthy, advanced and prosperous society. We are expected to become motivators and facilitators for the local community. The community can share existing problems and find solutions with the participation of KKN participants. The goals or targets that are expected to be achieved are: (a) fostering a sense of mutual cooperation among residents; (b) training on the application of teaching or covid-19 prevention guidance; (c) teach the public the introduction of personal protective equipment. The method of implementing the New Covid-19 Thematic KKN 2020 activity is carried out in the form of socialization and training by involving the government and the community directly and also online Abstrak Melalui kegiatan New KKN Tematik Covid-19 Tahun 2020 kita dituntut untuk meningkatkan kepedulian, kesadaran, dan ketahanan masyarakat menghadapi wabah covid-19 dalam upaya mewujudkan masyarakat sehat, maju, dan sejahtera. Kita diharapkan menjadi motivator dan fasilitator bagi masyarakat setempat. Masyarakat dapat berbagi permasalahan yang ada dan mencari solusi dengan partisipasi peserta KKN. Adapun tujuan atau target yang diharapkan dapat tercapai adalah: (a) menumbuhkan rasa solidaritas gotong royong antarwarga; (b) pelatihan penerapan pengajaran atau pembimbingan pencegahan covid-19; (c) mengajarkan masyarakat pengenalan alat pelindung diri. Metode pelaksanaan kegiatan New KKN Tematik Covid-19 Tahun 2020 dilakukan dalam bentuk sosialisasi dan pelatihan-pelatihan dengan melibatkan pemerintah dan masyarakat secara langsung dan juga daring.